The consumer purchase intention toward hybrid electric car: A utilitarian-hedonic attitude approach - Zamil, Ahmad M. A.; Ali, Saqib; Akbar, Minhas; Zubr, Vaclav; Rasool, Farhan (Frontiers in Environmental Science, 2023)
Environmental conditions are rapidly changing with every passing day worldwide. Degradation of ecological conditions has an adverse impact on human health. Carbon emission severely destroys greenhouse gases, CO2 is generated from different sectors, but the major portion of CO2 is generated from the transport sector. This environmental deterioration stimulates academicians and practitioners to study ecological consumption behaviour. Protecting the environment by reducing carbon emissions is a shared responsibility. In the current era, the world is shifting from conventional vehicles to electric vehicles or hybrid vehicles to control carbon emissions. This study examines the factors in predicting consumers' purchase intention toward hybrid vehicles through the S-O-R model and theory of consumption values (functional and non-functional values). This will help academics and policymakers to expand the penetration of this new and favourable green technology in terms of protecting the environment. For our study, we collected data from the three big cities of Punjab, i.e. (Multan, Sahiwal, and Lahore). In this study, 500 questionnaires were distributed, from which 245 were returned. In the first step, we provide detailed information about demographic variables. The structural equation model (SEM) is used for evaluating the impact of identified constructs. The study results conclude that functional values (except conditional value) and non-functional values (except social value responsibility) positively influence the consumer's attitude toward the intention to adopt hybrid electric vehicles. The reasons behind the results and implications for the practitioners and policymakers are discussed. Furthermore, directions for future research have also been suggested.